The Terrestrial Slugs of Northeastern North America - Lyle F. Chichester; Lowell C. Getz (Hello World!, 1973)
The term 'slug' is applied to those gastropod mollusks in which there has been a distinct trend towards the loss of the external shell. With one exception, all the terrestrial slugs which have been recorded from, or could be expected to be found in northeastern North America have entirely lost the external shell. Some forms still retain a small, plate-like remnant of the shell under the fleshy mantle; in others only granules or spicules of calcium carbonate buried in the mantle remain. The loss of the shell reduces the need for calcium and permits the animals to move through narrow spaces.